Performance benchmarking and analysis of lithium-sulfur batteries for next-generation cell design - Saeed Yari; Albin Conde Reis; Quanquan Pang; Mohammadhosein Safari (Nature Communications)
Abstract Lithium-sulfur batteries are emerging as strong contenders in energy storage; however, a cohesive design framework, systematic performance analysis and benchmarks remain absent. This study bridges this gap by examining recent advancements, with a focus on functional sulfur host materials, using a data-driven approach. Through a meticulous literature review, we digitize 866 galvanostatic cycling and rate capability plots, along with the collection of key host material properties—such as specific surface area and polysulfide binding/adsorption energy—as well as essential cell design parameters including sulfur loading, electrode formulation, and electrolyte-to-sulfur ratios, to standardize performance using specific energy and power metrics. This approach enables us mapping field advancements and identify impactful research contributions. Additionally, irrespective of materials chemistry, a comprehensive analysis of this database helps us to disclose general patterns that apply universally across all cells, highlight the most constructive and detrimental regions of the design-parameter space, and perceive potential synergies. These insights outline key areas for optimization, guiding future development of practical lithium-sulfur battery technology.